Human landscapes of the Late Glacial Period in the interior of the Iberian Peninsula: La Peña de Estebanvela (Segovia, Spain) (Quaternary International, 2012)
The chronostratigraphic framework of the Magdalenian in the interior of the Iberian Peninsula currently covers the period 21,440e21,040 cal BP (level 2 of the Cueva del Gato site at Epila, Province of Zaragoza) to 12,770e12,570 cal BP (level I of the La Peña de Estebanvela site, Ayllón, Province of Segovia). These dates embrace times of strong climatic oscillation, beginning with very rigorous environmental conditions (stage GS2) and ending with a temperate climate (Alleröd); over this period, extreme events such as Heinrich event 1 occurred. However, little information is available that would allow the environments through which human groups moved during the Late Last Glacial of the Iberian interior to be characterised. The La Peña de Estebanvela site is something of an exception in that its archaeological features allow the reconstruction of the surrounding environment, and provide information on how natural resources may have been used. The faunal remains represented at this site reﬂect changes in palaeoecology over time. Taphonomic analysis of recovered macromammals and lagomorphs shows that these animals were brought to the site, butchered and consumed. The available data on seasonality ﬁx the occupation of levels IeIII from the spring to the autumn. Certain types of wood were collected for use as ﬁrewood. Other elements found in the record (personal ornaments, mobiliary art and raw materials) provide evidence that the people that occupied the site moved over a more extensive territory.